Theoretical justification of a purposeful search of potential neurotropic drugs - Semenets, Anton; Suleiman, Marharyta; Georgiyants, Victoriya; Kovalenko, Sergiy; Kobzar, Natalia; Grinevich, Lina; Pokrovskii, Mikhail; Korokin, Mikhail; Soldatov, Vladislav; Bunyatyan, Vera; Perekhoda, Lina (ScienceRise: Pharmaceutical Science, 2020)
A targeted search for potential drugs of neurotropic action involves the choice of a basic “pharmacophore”, which is advisable to carry out on the basis of the achieved principle among the classes of chemical compounds where active pharmaceutical substances with high targeted activity have already been identified. Therefore, the pyrrolidine core, which is the basic fragment of nootropics of the racetam group, is promising for the rational design of biologically active compounds of nootropic action. Its combination with other heterocyclic fragments, in particular, the 1,2,4-triazole ring, allows for these “hybrid” molecules to expect a permanent change in the magnitude of the pharmacological effects. Creation of a virtual library of compounds, 3D-pharmacophore screening and molecular docking is a promising way to optimize a targeted search for substances with a given pharmacological activity. The aim. To optimize targeted search for new nootropic compounds. Materials and methods. The base generation for the virtual screening was carried out using the Marvin Sketch 20.5 software. For receptor-oriented flexible docking, the Autodock 4.2 software package was used. Results. New derivatives of 1-benzyl-4-pyrrolidin-2-one were selected as the object of the study. Based on the results of the 3D pharmacophore screening and molecular docking to nootropic targets of the virtual base compounds, scoring functions were calculated. A detailed analysis of the geometrical arrangement of “hit compounds” at the active sites of nootropic receptors (PDB ID: 5UOW, 5CXV, 6PV7) made it possible to formulate hypotheses regarding possible ways of interaction of “hybrid” compounds with biotargets. The activity of promising molecules with respect to the studied receptors can be realized by creating complexes between them, the stability of which is ensured mainly due to the energetically favourable geometric arrangement of ligands in the active center of these acceptors, the formation of hydrogen bonds between them, and intermolecular electrostatic and donor-acceptor interactions. Conclusions. Structural modification of the pyrrolidine ring by combining with 1,2,4-triazole scaffold containing substituents of various electronic nature has been proposed. Using 3D-pharmacophore screening, the virtual base of 1-benzyl-4-pyrrolidin-2-one derivatives was analyzed in order to search among them for new molecules of nootropic action. Docking studies have identified a promising group of derivatives of 1-benzyl-4 (4-R-5-sulfanylidene-4,5 dihydro-1H-1,2,4-triazol-3-yl) pyrrolidin-2-one, which have affinity for nootropic biotargets and are promising for further synthetic and pharmacological studies